Promotion of physical activity-related health competence in physical education: study protocol for the GEKOS cluster randomized controlled trial - Stephanie Haible; Carmen Volk; Yolanda Demetriou; Oliver Höner; Ansgar Thiel; Ulrich Trautwein; Gorden Sudeck (BMC, 2019)
Abstract Background One central goal of physical education in many countries is to empower students to be physically active throughout their lifespan. Physical activity-related health competence (PAHCO) encompasses physical, cognitive, and motivational elements associated with the individuals' ability to be physically active in a health-enhancing way. To date, there is a lack of empirical evidence concerning effective programs and methods to promote PAHCO in physical education. The purpose of this study is to examine to what extent a health and physical fitness-related program that includes learning tasks integrating theoretical and practical elements promotes students' PAHCO in physical education. Design/methods This study is a cluster randomized controlled trial that compares two physical education intervention programs on health and physical fitness (IG-run, IG-game play) with regular physical education lessons (CG-run, CG-game play) in secondary schools in Germany. Forty-eight physical education classes (ninth grade) were recruited and randomly allocated to the four study groups. The intervention programs include six physical education lessons on health and physical fitness and only differ in the type of physical activity that is executed (running and jumping vs. small-sided games). The students' PAHCO is examined both pre- and post-intervention and after 8-12 weeks of follow-up. We also determine various process variables during the intervention period to analyze the intervention fidelity. Discussion The results of this study provide evidence on whether a combination of theoretical and practical elements in physical education can enhance students' PAHCO. Beyond that, our process analyses will allow differentiated insights into the mechanism of how the intervention programs work. Trial registration German Clinical Trials Register (DRKS), DRKS-ID: DRKS00016349. Retrospectively registered on 10 January 2019.